Hubungan Harga Diri dengan Kecemasan Sosial pada Siswa SMP Al – Washliyah Medan - Hermansyah; Nurul Azmi Saragih (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
there is also anxiety that arises due to stimulation from outside. Stimulation from outside can be from social situations or interactions with other people. Anxiety is often experienced by most people, especially in adolescence, when individuals are in a new social environment or are in a social environment that is different from the social environment in which the individual is usually located. above opinion, the formulation of the problem in this study is how is the Relationship Between Self-Esteem and Anxiety in Adolescents of SMP AL - WASHLIYAH. So the objective obtained in this study is how is the Relationship Between Self-Esteem and Anxiety in Adolescents of SMP AL - WASHLIYAH Medan. The approach used in this study is a qualitative approach. A qualitative approach is a research procedure that produces descriptive data in the form of written or spoken words of people and observable behavior. A qualitative approach has natural characteristics (Natural serfing) as a direct source of data, descriptive, the process is more important than the results. So it can be concluded that the two variables are correlated or there is a relationship. Furthermore, from the results of the correlation test, it is known that in this study the correlation between self-concept and social anxiety has a Pearson correlation value of -0.534. This shows that there is a negative relationship between the self-concept variable and social anxiety, which means that the higher the self-concept of the subject, the lower the social anxiety he has, and vice versa.